The Difference Coagulopathy Factor and Interleukin-6 between Survival and Non-survival Patients COVID-19 - Putra, Yoshua Arif; Mutiara, Mutiara (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Coronavirus disease 2019 (COVID-19) was caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus. SARS-CoV-2 infection can result in coagulopathy and an increase in inflammatory responses. Numerous studies have shown a significant difference in interleukin levels and coagulopathy parameters such as platelet, aPTT, PT, and D- dimer between survivor and non-survivor patient COVID-19. Aim: The purpose of this study is to compare the age, coagulopathy characteristics, and interleukin-6 levels of non-survival versus survival patients. COVID-19. Methods: A cross-sectional retrospective study was conducted on COVID-19 patients. The diagnostic criteria are based on the Indonesian Ministry of Health’s recommendations. The patient’s blood was analyzed in the hospital’s central laboratory. Patients are classified into two groups based on their likelihood of surviving: non-survival and survival. SPSS version 22 was used to analyze the data. Results: A total of 557 patients with COVID-19 were included in this study. Patients were categorized into 146 non-survival and 411 survival subgroups. There was a significant difference in the mean age, coagulopathy parameters, and interleukin-6 expect platelets between non-survival and survival outcomes in COVID-19 patients. Conclusion: This study demonstrated a statistically significant difference in PT, aPTT, D-Dimer, and interleukin-6 levels between the non-survival and survival groups of COVID-19.